Research trends in humanitarian logistics and sustainable development: A bibliometric analysis - Muhammad Khan; Gohar Saleem Parvaiz; Alisher Tohirovich Dedahanov; Muhammad Iqbal; Bae Junghan (Cogent Business & Management, 2022)
Sustainable development (SD) has become a prevalent topic in the logistics discipline. Hence, the attention of researchers to humanitarian logistics (HL) in SD has been increasing. Therefore, the study applied a literature review in a bibliometric methodology, and feasibly reached a total of 112 publications published in world-class journals from the chosen databases. The findings show an increasing trend in the number of studies in this area, and that most of the studies were published in the last three years. Humanitarian Organizations (HOs) have a responsibility to save victims and decrease the distress of persons for SD during difficult times through fast, fair, and safe HL, which is possible through an effective HL operation. This study offers the first bibliometric investigation in the field that could serve as a theoretical reference point for future investigations and as a managerial tool, recognizing the urgent need for a careful understanding of how sustainability can be integrated into HL.
Keywords: 650; bibliometric literature review; Humanitarian logistics; humanitarian supply chain; relief logistics; sustainable development